2010
DOI: 10.1111/j.2042-3306.2010.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of endurance training on total tract apparent digestibility, total mean retention time and faecal microbial ecosystem in competing Arabian horses

Abstract: SummaryReasons for performing study: In endurance horses, commonly fed 80% forage, energy is provided mainly by VFA produced in the hindgut during cell wall degradation, but cell wall digestibility has been reported to be impaired by exercise. Objectives: To assess the influence of a long-term endurance conditioning on cell wall digestion in horses. Methods: The total tract apparent digestibility of dry matter, organic matter and fibrous constituents, solid and liquid total mean retention time and the faecal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
2
11
0
2
Order By: Relevance
“…Matthewman and Dijkman (1993) reported better mixing of digesta in working animals resulting in improvement in microbial profile and digestibility. Similar increase in digestibility of DM, OM and NDF was also reported in horses after endurance work (Goachet et al 2010).…”
Section: Feed Consumption Nutrient Intake and Apparent Digestibilitysupporting
confidence: 66%
“…Matthewman and Dijkman (1993) reported better mixing of digesta in working animals resulting in improvement in microbial profile and digestibility. Similar increase in digestibility of DM, OM and NDF was also reported in horses after endurance work (Goachet et al 2010).…”
Section: Feed Consumption Nutrient Intake and Apparent Digestibilitysupporting
confidence: 66%
“…In the present study increasing dietary protein levels had an impact on the digestibility coefficients of CP, NDF, and ADF and tended to have an impact on the digestibility coefficients of DM and OM for horses subjected to intense exercise. Goachet et al (2010) reported higher values for the DM digestibility coefficient, 67.7% and 69.2%, for intensely exercising horses with DMI of 1.7% of BW. According to Goachet et al, conditioning had an impact on digestibility, and this impact improved DM, OM, and NDF digestibility.…”
Section: Discussionmentioning
confidence: 89%
“…A linear increase in digestible protein was expected on the basis of the linear increase of CP intake and linearly increasing response of the CP digestibility coefficient. Anywise, all the positive digestible effects are beneficial for exercising horses, which need an efficient and highly digestible diet (Goachet et al, 2010).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…2010). A 2 year study of competing Arabian endurance horses found a tendency for improved feed digestibility after training suggesting an influence of long‐term endurance training on cell‐wall digestibility in horses (Goachet et al . 2010).…”
Section: Nutrition Of the Exercised Horsementioning
confidence: 99%